1996
DOI: 10.1099/00221287-142-9-2375
|View full text |Cite
|
Sign up to set email alerts
|

The presence of two S-layer-protein-encoding genes is conserved among species related to Lactobacillus acidophilus

Abstract: BCCM/LMGPreviously w e have shown that the type strain of Lactobacillus acidophilus possesses two S-protein-encoding genes, one of which is silent, on a chromosomal segment of 6 kb. The 5-protein-encoding gene in the expression site can be exchanged for the silent S-protein-encoding gene by inversion of this slp segment. In this study the presence of S-protein and corresponding Sprotein-encoding genes of strains belonging to species that are closely related to L acidophilus was determined. All strains investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 9 publications
3
59
0
Order By: Relevance
“…The three distillery isolates had identical tuf alleles and were again most closely related to L. helveticus and L. gallinarum (see Supplementary Fig. B available in IJSEM Online), confirming the value of this gene as a reliable indicator of phylogenetic relationships within this group of bacteria (Chavagnat et al, 2002).Lactobacilli of the L. acidophilus group, apart from L. johnsonii and L. gasseri, possess a highly variable surfacelayer protein (Boot et al, 1996) that has been used as a taxonomic tool for identification of L. crispatus (Horie et al, 2002). We amplified and sequenced partial slp genes from the three distillery isolates and L. gallinarum DSM 10532 T .…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…The three distillery isolates had identical tuf alleles and were again most closely related to L. helveticus and L. gallinarum (see Supplementary Fig. B available in IJSEM Online), confirming the value of this gene as a reliable indicator of phylogenetic relationships within this group of bacteria (Chavagnat et al, 2002).Lactobacilli of the L. acidophilus group, apart from L. johnsonii and L. gasseri, possess a highly variable surfacelayer protein (Boot et al, 1996) that has been used as a taxonomic tool for identification of L. crispatus (Horie et al, 2002). We amplified and sequenced partial slp genes from the three distillery isolates and L. gallinarum DSM 10532 T .…”
mentioning
confidence: 62%
“…Lactobacilli of the L. acidophilus group, apart from L. johnsonii and L. gasseri, possess a highly variable surfacelayer protein (Boot et al, 1996) that has been used as a taxonomic tool for identification of L. crispatus (Horie et al, 2002). We amplified and sequenced partial slp genes from the three distillery isolates and L. gallinarum DSM 10532 T .…”
mentioning
confidence: 99%
“…acidophilus', as suggested by Fujisawa et al (1996). It has been reported that S-layers, which are composed of a single protein species with a relative molecular mass of 43 000-46 000, commonly occur in Lactobacillus isolates that belong to genome clusters A1-A4 within the L. acidophilus group, but are absent from isolates that belong to genome clusters B1 and B2 (Masuda, 1992;Mukai & Arihara, 1994;Boot et al, 1996). Our previous studies showed that cell-surface protein profiles of L. acidophilus JCM 1038 and JCM 1039 from chicken intestine were apparently different from those of reference cells that belonged to L. acidophilus group A (Mukai & Arihara, 1994).…”
mentioning
confidence: 88%
“…1, express S-layer proteins on their cell surface (Masuda, 1992;Mukai & Arihara, 1994;Boot et al, 1996;Callegari et al, 1998). We analysed the cell-surface protein patterns of all six strains in comparison with those of reference strains.…”
Section: Strains Jcm 1038 Jcm 1039mentioning
confidence: 99%
“…DNA hybridization with specific probes to S-layer protein genes slpA and slpB of L. acidophilus revealed the presence of S-layer genes in other members of the acidophilus complex A, i.e. Lactobacillus crispatus, Lactobacillus amylovorus and Lactobacillus gallinarum (Boot et al, 1996). However, L. gasseri ATCC 33323…”
Section: Discussionmentioning
confidence: 99%